Students learning needs in science form one - Nur Suhaidah Sukor (Creative Education, 2022)
This study discusses the step by step in building the STEM Inspirational Module. This research uses a purposive sampling technique that collecting data from panel of expert (lecturer), six teachers and 20 students. Research instruments used are questionnaires and structured interviews conducted to both teachers and students. Data were collected and mean analysis and percentages were carried out. The findings show that educational innovation can help teachers overcome the time constraints in designing lesson plan with STEM Activities. STEM Inspirational Module Kit is easy to handle and is readily available for teachers to use. Furthermore, the modules are based on low cost and easy-to-use materials and tools.